One-Pot Protolignin Extraction by Targeted Unlocking Lignin–Carbohydrate Esters via Nucleophilic Addition–Elimination Strategy - Yuhan Lou; Xinyue Sun; Yanyan Yu; Suqing Zeng; Yilin Li; Yongzhuang Liu; Haipeng Yu (Research, 2023)
Protolignin extraction can facilitate structure elucidation and valorization of lignin in biorefinery, but is rather challenging due to the complex chemical bonds present. Here, we developed the in situ generated NH3-reline (IGNR) system to realize one-pot protolignin extraction from lignocellulose. In the IGNR system, reline consisting of choline chloride and urea acted as both a solvent and a nucleophile generator, and the nucleophilic addition–elimination mechanism was verified by model compound studies. The in situ generated NH3 could precisely cleave the lignin–carbohydrate esters in lignocellulose with a near-quantitative retention of carbohydrates. The extracted IGNR–Protolignin exhibited native lignin substructure with high molecular weight and high β-O-4′ content (41.5 per 100 aromatic units). In addition, the up-scaled kilogram reaction demonstrated the feasibility of the IGNR system for potential industrial application in a green and sustainable pathway. This work represents a breakthrough toward protolignin extraction in practice with the future goal of achieving total biorefinery.